A family of martingales generated by a process with independent increments - Sole, J.L.; Utzet, F. (Інститут математики НАН України, 2008)
An explicit procedure to construct a family of martingales generated by a process with independent increments is presented. The main tools are the polynomials that give the relationship between the moments and cumulants, and a set of martingales related to the jumps of the process called Teugels martingales.